Experiment Analysis of Concrete's Mechanical Property Deterioration Suffered Sulfate Attack and Drying-Wetting Cycles. (19th December 2017) - Tian, Wei; Han, Nv
Abstract : The mechanism of concrete deterioration in sodium sulfate solution is investigated. The macroperformance was characterized via its apparent properties, mass loss, and compressive strength. Changes in ions in the solution at different sulfate attack periods were tested by inductively coupled plasma (ICP). The damage evolution law, as well as analysis of the concrete's meso- and microstructure, was revealed by scanning electron microscope (SEM) and computed tomography (CT) scanning equipment. The results show that the characteristics of concrete differed at each sulfate attack period; the drying-wetting cycles generally accelerated the deterioration process of concrete. In the early sulfate attack period, the pore structure of the concrete was filled with sulfate attack products (e.g., ettringite and gypsum), and its mass and strength increased. The pore size and porosity decreased while the CT number increased. As deterioration progressed, the swelling/expansion force of products and the salt crystallization pressure of sulfate crystals acted on the inner wall of the concrete to accumulate damage and accelerate deterioration. The mass and strength of concrete sharply decreased. The number and volume of pores increased, and the pore grew more quickly resulting in initiation and expansion of microcracks while the CT number decreased.